Is the sensitivity to ammonium nutrition related to nitrogen accumulation? - Aschi-Smiti, Faouzi Horchani, Rim Hajri and Samira (Current Botany, 2011)
Nitrate and ammonium can be used as nitrogen sources by most plant species although plant response to continuous ammonium nutrition is species dependent. In the present study, the effect of the nitrogen source (nitrate and ammonium) on growth, photosynthetic parameters, nitrogen content and nitrogen assimilating-enzymes (nitrate reductase, glutamine synthetase and glutamate dehydrogenase) was investigated in wheat (Triticum aestivum L.), tomato (Solanum lycopersicum L.) and lucerne (Medicago truncatula L.). Obtained results showed that these plant species vary in their sensitivity to NH4+ nutrition, with wheat to be highly sensitive, tomato moderately sensitive and lucerne tolerant to ammonium nutrition. For the three plant species, the growth reduction was correlated closely to ammonium accumulation in leaves. Moreover, contrary to that was observed for wheat plants, glutamine synthetase and glutamate dehydrogenase activities were higher in roots than in leaves, for tomato and lucerne plants. Taken together, these data suggest that the site of ammonium assimilation is a key factor controlling tolerance to ammonium nutrition in the different plant species, with plants being more tolerant when ammonium is assimilated in roots.